Race and Neoliberalism in the Labour Market Integration of International Student Graduates in Canada - Ellis, Everton (Journal of International Students, 2023)
This paper illustrates the mutually constitutive processes of race and neoliberalism in the labour market navigation and integration for Black Caribbean and South/Southeast Asian international student graduates in Canada. The data was gathered from recent international students and key informants in Canada’s immigration policy circle using semi-structured interviews. The paper reveals that international student graduates are constrained to seek out precarious and low-skilled forms of employment and participate in a labour market that profits from cheap, exploitable flexible labour. Participants in areas outside the populous Greater Toronto and Hamilton Area are perceived as contingent workers. The paper concludes on the salience using a non-racial analysis of neoliberalism to interpret the postgraduation employment of international students.